Upaya Orang Tua dalam Menanamkan Sikap Religiusitas Remaja di Masjid Al-Ma’ruf Desa Sukajaya Kecamatan Lembang Kabupaten Bandung Barat - Nova Amelia Putri; Asep Dudi Suhardini; Nurul Afrianti (Bandung Conference Series: Islamic Education, 2024)
Abstract. The role of parents in instilling religiosity in adolescents is a very important aspect in character and moral formation. In shaping the religious attitudes of adolescents, in particular, this study examines the role played by parents in shaping the religious attitudes of adolescents, focusing on the influence carried out in the environment of the Al-Ma'ruf mosque. The objectives of this study are: 1) To find out the description of the profile of adolescents in the Al-Ma'ruf Mosque, Sukajaya Village, Lembang District, West Bandung Regency, 2) To find out the description of religious behavior of adolescents in the Al-Ma'ruf Mosque, Sukajaya Village, Lembang District, West Bandung Regency, 3) To find out how the role of parents in instilling religious attitudes of adolescents in the Al-Ma'ruf Mosque, Sukajaya Village, Lembang District, West Bandung Regency, 4) To find out and describe the strategies of parents in instilling religiosity attitudes in adolescents at the Al-Ma'ruf Mosque, Sukajaya Village, Lembang District, West Bandung Regency. This study uses a qualitative approach with in-depth interview techniques with parents and adolescents who are active in the mosque. The results of the study show that parents have a central role in influencing the development of adolescents' religious attitudes through various ways, including religious education, role models, and active participation in religious activities. Abstrak Peran orang tua dalam menanamkan sikap religiusitas pada remaja merupakan aspek yang sangat penting dalam pembentukan karakter dan moral. Dalam membentuk sikap religius remaja, khususnya dari studi ini mengkaji peran yang dimainkan oleh orang tua dalam membentuk sikap religius remaja, dengan fokus pada pengaruh yang dilakukan di lingkungan masjid Al-Ma'ruf. Adapun tujuan dari penelitian ini yaitu: 1) Untuk mengetahui gambaran profil remaja di Masjid Al- Ma’ruf Desa Sukajaya Kecamatan Lembang Kabupaten Bandung Barat, 2) Untuk mengetahui gambaran perilaku religius remaja di Masjid Al-Ma’ruf Desa Sukajaya Kecamatan Lembang Kabupaten Bandung Barat, 3) Untuk mengetahui bagaimana peran orang tua dalam menanamkan sikap religiusitas remaja di Masjid Al-Ma’ruf Desa Sukajaya Kecamatan Lembang Kabupaten Bandung Barat, 4) Untuk mengetahui dan mendeskripsikan strategi orang tua dalam menanamkan sikap religiusitas pada remaja di Masjid Al-Ma’ruf Desa Sukajaya Kecamatan Lembang Kabupaten Bandung Barat. Pada penelitian ini menggunakan pendekatan kualitatif dengan teknik wawancara mendalam terhadap orang tua dan remaja yang aktif di masjid tersebut. Hasil penelitian menunjukkan bahwa orang tua memiliki peran sentral dalam mempengaruhi perkembangan sikap religius remaja melalui berbagai cara, termasuk pendidikan agama, teladan, dan partisipasi aktif dalam kegiatan keagamaan.